2011
DOI: 10.1166/jnn.2011.3576
|View full text |Cite
|
Sign up to set email alerts
|

<I>In Vitro</I> Antifungal Activity and Toxicity of Itraconazole in DMSA-PLGA Nanoparticles

Abstract: Itraconazole (ITZ) is a drug used to treat various fungal infections and may cause side effects. The aim of this study was to develop and evaluate the in vitro activity of DMSA-PLGA nanoparticles loaded with ITZ against Paracoccidioides brasiliensis, as well as their cytotoxicity. Nanoparticles were prepared using the emulsification-evaporation technique and characterized by their encapsulation efficiency, morphology (TEM), size (Nanosight) and charge (zeta potential). Antifungal efficacy in P. brasiliensis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…It has become apparent that the development of nanotechnology for the treatment of infectious diseases, particularly skin disease, involves two major areas: The first utilizes materials that at the nanoscale have inherent antimicrobial properties (Hemmila et al, 2010), and the second incorporates known therapeutics into nano-vehicles in order to enhance delivery and improve efficacy (Cunha-Azevedo et al, 2011; Dominguez-Delgado et al, 2011; Kumar et al, 2011). The ideal approach to develop a topical therapy for microbial infection in skin would utilize a nanomaterial that has both inherent and potent antimicrobial properties and the ability to serve as a nano-vehicle would be ideal.…”
Section: Introductionmentioning
confidence: 99%
“…It has become apparent that the development of nanotechnology for the treatment of infectious diseases, particularly skin disease, involves two major areas: The first utilizes materials that at the nanoscale have inherent antimicrobial properties (Hemmila et al, 2010), and the second incorporates known therapeutics into nano-vehicles in order to enhance delivery and improve efficacy (Cunha-Azevedo et al, 2011; Dominguez-Delgado et al, 2011; Kumar et al, 2011). The ideal approach to develop a topical therapy for microbial infection in skin would utilize a nanomaterial that has both inherent and potent antimicrobial properties and the ability to serve as a nano-vehicle would be ideal.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few groups previously reported PLGA-ITZ nanoparticles for in vitro antifungal activity, [13][14][15] but their formulations were not systematically characterized for in vivo study, and no pharmacokinetics have ever been completed to explore the formulation's capability of intravenous injection and sustained release. We herein synthesized, characterized, and optimized the formulation for parenteral administration.…”
mentioning
confidence: 99%
“…A subsequent study showed that the nano-D-AMB is highly captured in the lungs, liver, and spleen of mice (Souza et al, 2015). DMSA-PLGA NPs loaded with ITZ have also been studied against P. brasiliensis and the PLGA-ITZ had lower MICs compared to ITZ alone with less cytotoxicity compared to the free drug (Cunha-Azevedo et al, 2011). Gallic acid is a secondary metabolite derived from plants such as Paeonia rockii, Astronium sp., and Syzygium cumini, among others.…”
Section: Aspergillosismentioning
confidence: 99%